That dirty black bag. Season 1 [videorecording (DVD)] - Booth, Douglas, 1992-; Cooper, Dominic, 1978-; Gillen, Aidan, 1968-; Fimmel, Travis, 1979-; Sultan, Niv; Caprino, Guido; Cooke, Christian, 1986-; Williams, Rose, 1994-; Joseph, Paterson; Boyle, Zoe (AMC Studios, 2022)
Over eight long days two men dramatically clash: McCoy, an incorruptible sheriff with a dark past, and Red Bill, a dirty, taciturn bounty killer trapped in a desire for vengeance that cannot be fulfilled.